The Increased Knowledge and First Aid Skills of Burns on Health Cadres with Health Education and Simulation - Linda Ayu Lestari; Nurul Fatwati Fitriana (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Burns rank sixth as the cause of accidental injuries. It can cause disability and death if it is not handled in the correct ways. Appropriate handling is based on adequate knowledge and skills. Lack of knowledge in carrying out the first aid made the cadres cannot take care of burns well. This research aimed to find out the effect of health education and simulation on the health cadres' knowledge and first aid skills of burns in Ketenger Village. This was pre-experimental quantitative research with One Group Pre and Post-test Design. The population in this study were all cadres of Ketenger Village. The sample was taken using an accidental sampling method. The number of samples was 30 people. The research data were collected using questionnaires and observation sheets. Then the data were analyzed using the Wilcoxon test. The results of the research indicated that before and after the health education was given the average value of the cadres' knowledge was 11.83 and 15.57 respectively. Then, before and after the simulation, the average value of cadres skills was 2.83 and 8.63 respectively. Based on the bivariate analysis using the Wilcoxon test, the p-value of both knowledge and skills was 0,000 < 0,05. Health education and simulation have an effect on the cadres' knowledge and skills in the first aid of burns.